Improvement plan to reduce costs in an LPG packaging plant, 2024 - Geldres Marchena, Teodoro Alberto; Guarniz Rodríguez, Oscar Enrique; Jiménez Acuña, Sergio Rafael (LACCEI, 2024)
This work applied engineering knowledge to improve the situation of an LPG bottling plant, focusing on reducing costs by solving problems identified in an initial analysis. A diagnosis was made to prioritize the most harmful problems, and various alternatives were developed, choosing one based on specific criteria and restrictions. These alternative included standards such as Law No. 29783 on Occupational Safety and Health, and standards such as API RP 1170, NFPA 58, ASME B31.5, API RP 1162, and ASME BPVC, Section VIII for pressure vessels. ISO 9001:2015, ISO 45001:2018, EN 12807:2020 and ISO 14001:2015 were also applied to improve service quality, protect workers, design steel cylinders and manage environmental performance. Specific indicators allowed the development of the problems to be measured, and simulations were carried out in ProModel and Monte Carlo to validate the design. In the 5S tool upgrade, it was reduced from 77% to 23%; in preventive and autonomous maintenance, from 97% to 3%; and in the PDCA tool, it went from 45% to 55%. The economic evaluation showed a minimum rate of return of 18.49%, a NPV of S/. 34,213.71 and an IRR of 94%, indicating that the proposal is profitable. The B/C was 1.93